BIOLOGICAL GROWTH QUALITY OF CARASOBARBUS LUTEUS FROM EUPHRATES IN AL- MUTHANNA PROVINCE - Alasadiy, Y. D. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Results of current study represents the first investigation on age groups and growth of Carasobarbus luteus from two stations of the Euphrates in Al- Muthanna province, during the period from September 2017 to March 2018.A total of 155 samples were caught belonging this fish species . age group comprised five (II+-VI+) for males and six (II+-VII+) for females with dominant III + age group in both sexes. The annual increment in length was decreased with the increase in age group, while the annual increment in weight was the highest in the first year and increase with age, except for VI+ year for males. The regression coefficient (b) indicated that the growth modality of Carasobarbus luteus was Allometric in males and isometric in females. mean values of condition factor from 1.06699 (IV+) to 1.51979 (II+) in males and between 1.156865(VII+) to 1.558341(IV+) for females, statistical analysis showed significant differences(P≤0.05) between males and females in values of condition factor .Growth models of Von Bertalanffy were( L∞=30 cm, K=0.15, to= -0.213) for both sexes. The current study found that this fish does not reach large, ages and the female growth is better than male.